Early Diagnosis of Childhood Cancer in Peru: Importance and stretagies - Chávez-Paredes, Sharon L. (2024)
Early diagnosis of childhood cancer is important to improve the survival of pediatric patients and avoid the high mortality that comes with late diagnosis of this pathology. This narrative review article presents the importance of early diagnosis of childhood cancer and the various strategies developed in recent years in Latin America and Peru in conjunction with international organizations.